Self-Confidence Differences Between Extracurricular-Active and Extracurricular-Inactive Students - Rosida, Hilda (Southeast Asian Journal of Technology and Science, 2025)
This study aims to compare the level of self-confidence between adolescents who are active and inactive in extracurricular activities in Kota Serang. This study employed a quantitative approach using a comparative method. The population of this study consisted of adolescents in Kota Serang, and the sample was determined using Isaac and Michael’s table. The research instrument was a Likert-scale questionnaire measuring self-confidence. Data analysis included descriptive statistics, validity and reliability testing, normality and homogeneity testing, and an independent samples t-test. The results indicate that involvement in extracurricular activities has a positive effect on increasing adolescents’ self-confidence, suggesting that schools and related educational institutions should further encourage adolescent participation in extracurricular activities as a means of psychological and social development.